Pengaruh Digital Marketing, Social Media Influencer Terhadap Niat Beli Produk Fashion Pada Generasi Milenial Melalui Customer Online Review di Instagram - Amelia Ibnu Wasiat, Friana; Bertuah, Eka (CV. Lafadz Jaya, 2022)
Various aspects of human life have been touched and even changed as a result of the adoption of information and communication technology. We are currently in the industrial revolution 4.0 marked by digital technology. The entry of this era of disruption makes everything easier, faster and cheaper. This causes changes in Consumer behavior. Instagram has become a phenomenon in itself among social media users, especially teenagers. Many people use Instagram as a means to do business by uploading photos of the products they choose. This study examines the effect of digital marketing and social media influences on purchase intention with the online Consumer review variable as the intervening variable. Primary data collected using a survey method by distributing questionnaires to respondents who use the Instagram application to purchase fashion products. The questionnaires collected were 170 respondents, the data was then processed by path analysis method. Based on the results of research analysis there is a direct influence between digital marketing and social media influencers on online Consumer reviews, there is a direct influence of digital marketing, social media influencers and online Consumer reviews on purchase intention, however, the online Consumer review variable is not proven as an intervening variable between digital marketing and social media influencers on purchase intention.